INTEGRATIVE APPROACH AND INTERDISCIPLINARY CONNECTIONS IN TEACHING FINE ARTS - Abdullayeva Fotima Safar qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the use of an integrative approach and interdisciplinary connections in teaching fine arts. It highlights the importance of combining artistic education with other academic disciplines such as history, literature, science, and technology to enhance students’ creativity, critical thinking, and problemsolving skills. The study examines pedagogical strategies for effective integration and demonstrates how interdisciplinary methods improve learning outcomes, engagement, and the development of artistic competencies.